Rancang Bangun Mesin Pengering Bilah Bambu untuk Peningkatan Produktivitas Bambu Laminasi - Pratiwi, Ilham Ayu Putri; Bahari, Galuh (Jurnal Mekanik Terapan, 2025)
Laminated bamboo is an engineered composite product made from dried and bonded bamboo strips, offering high potential as an eco-friendly material for construction and furniture applications. One of the critical steps in its production process is the drying of bamboo strips, which aims to reduce moisture content and prevent mold, cracking, and delamination. This study aims to design an energi-efficient bamboo strip drying system to enhance the productivity of the laminated bamboo industry. The system design includes a modular drying chamber, a boiler-based heating system with a centrifugal blower, and corrosion-resistant materials such as stainless steel SS304. Thermal energi demand was calculated using convection heat transfer and total thermal resistance approaches, resulting in a required energi of 212240.42 kJ to dry 250 bamboo strips per cycle in an hour. Computational Fluid Dynamics (CFD) simulations indicate uniform temperature and airflow distribution inside the drying chamber. The thermal efficiency of the system reaches 97.4%, indicating its suitability for industrial application. These findings provide a foundation for developing standardized, efficient, and sustainable bamboo drying systems.